Membrane traffic in cytokinesis. (26th October 2005) - Matheson, J.; Yu, X.; Fielding, A.B.; Gould, G.W.
Abstract : A crucial facet of mammalian cell division is the separation of two daughter cells by a process known as cytokinesis. An early event in cytokinesis is the formation of an actomyosis contractile ring, which functions like a purse string in the constriction of the forming furrow between the cells. Far less well characterized are the membrane-trafficking steps which deliver new membrane to the cell surface during the plasma membrane expansion known to accompany furrow formation. It is now clearly established that the plasma membrane at the cleavage furrow of mammalian cells has a distinct lipid and protein composition from the rest of the plasma membrane. This may reflect a requirement for both increased surface area during furrowing and for the co-ordinated delivery of intracellular signalling or membrane re-modelling activities to the correct spatial coordinates during cleavage. In this review, we discuss recent work within the area of membrane traffic and cytokinesis.